INTEGRATING VLOGGING AND HIGHER-ORDER THINKING SKILLS IN UNIVERSITY ENGLISH SPEAKING INSTRUCTION: EVIDENCE FROM A COMPARATIVE CLASSROOM STUDY - Zulfitri, Nurlaili (JURNAL ILMU PENDIDIKAN, 2026)
The integration of digital technology and higher-order thinking skills (HOTS) has become increasingly important in English language education, particularly in developing university students’ communicative competence and 21st-century skills. This study examined the use of vlog-based learning integrated with HOTS-oriented activities in university English speaking instruction. The study employed a comparative pretest–posttest classroom design supported by descriptive qualitative data. The participants were students enrolled in the English Education Study Program at Universitas Muslim Nusantara Al Washliyah, Medan, Indonesia. Data were collected through speaking assessments, classroom observations, documentation, and student responses to the learning activities. The quantitative data were analyzed descriptively by comparing students’ learning gains between the vlog-and-HOTS group and the conventional-learning group. The reported statistical analysis indicated a higher mean gain score for the vlog-and-HOTS group (M = 0.5713) than for the conventional group (M = 0.4380). The statistical output reported in the research documentation also indicated a significant difference between the groups (F = 35.349, p < .001). Qualitative findings suggested that vlog-based activities provided students with opportunities to research topics, discuss ideas, prepare scripts, practice speaking, produce digital content, collaborate with peers, and reflect on their performance. Overall, the findings suggest that integrating vlogging with HOTS-oriented learning activities can provide a meaningful learning environment for developing university students’ English speaking performance and supporting 21st-century competencies. Since the original SPSS dataset was unavailable for reanalysis, the statistical findings are reported based on the aggregated results available in the research documentation.